ANALISIS PENILAIAN KETERAMPILAN KEWARGANEGARAAN SISWA KELAS X IPS MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKN) DI SMA NEGERI 1 SUKOHARJO PADA SEMESTER II TAHUN AJARAN 2016/2017 - Wulandari, Dewi; Nuryadi, Muh Hendri, Wijianto (Educitizen, 2017)
ABSTRACTAssessment analysis of the tenth graders social science civic skills at courses subjects Pancasila and Civic Eduaction in Negeri 1 Sukoharjo high school second semester academic year 2016/2017 is conducted from the planning stage of civic skills assessment, preparation of civic skills assessment instrument, data collection of civic skills, processing and analyzing data of civic skills assessment. The purpose of this study was to analyze assessment instrumen, theacher constraints and solution to overcome obstacles in organizing civic skills assessment (intellectual and participatory civic skills) of the tenth graders Social Science at courses subjects Pancasila And Civic Eduaction in Negeri 1 Sukoharjo High School second semester academic year 2016/2017. This research is included in qualitative descriptive research by using purposive sampling technique. The subjects of this study include teachers of Pancasila and Civic Education course subject and ten graders of Social Science proficiency. The data collection technique is done by technically studying documents, interviews, oral test and observation.The technique of data analysis is done by data reduction, data presentation, conclusion and verification. The result of this research shows that the instrument of intellectual civic skills developed by the teachers of Pancasila and Civic Education ten class Social Science at Negeri 1 Sukoharjo High School in second semester academic year 2016/2017 less meet the content validity and construct validity because it is less able to reflect predetermined competency. and does not measure theoritical construct of the ability to analyze, ability to evaluate, ablility to take and defend an posotion of public issue. While the participatory civic skills asessment instrument developed by the teachers of Pancasila and Civic Education has fullfied the content validity because it has measured the predetermined competency. However, the participatory civic skills assessment instrument developed by the teachers of Pancasila and Civic Education ten class Social Science at Negeri 1 Sukoharjo High School in second semester academic year 2016/2017 lacks the construct validity but it is unable to measure the theoritical constructs of monitoring ability and influence ability. Obstacles faced by the teachers of Pancasila and Civic Education ten class Social Science at Negeri 1 Sukoharjo High School in preparing the instrument of civic skills asessment actually lies in the level of ability or competence possessed by the teacher it self in conducting the asessment. Solution to overcome teacher obstacles in formulating student civic skills asessement tool can be done throught the improvement of teacher competence.  Keyword: Learning Assessment Instrument, Intellectual Civic Skills, Participatory Civic Skills.